2023
DOI: 10.1186/s12891-023-06323-y
|View full text |Cite
|
Sign up to set email alerts
|

Association of bone mineral density with trichlorophenol: a population-based study

Abstract: Background Trichlorophenols (TCPs) are metabolites of several organochlorine chemicals, including chlorobenzene, hexachlorocyclohexane, and chlorophenoxy acid, present in air, surface water, soil, and sediment. Many studies have shown that endocrine disruptors (EDs)may contribute to decreased bone mass and the increased risk of osteoporosis. However, the relationship between TCP and bone mineral density (BMD) has not been studied yet. Methods We co… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 30 publications
0
1
0
Order By: Relevance
“…The current era of rapid global economic development characterized by various industrial processes, including increased production of automobiles, tobacco, cleaning products, building materials, and other household products, has made VOCs more common in the human environment [23][24][25][26][27]. Several studies have demonstrated that some VOCs, such as Perfluoro and Polyfluoroalkyl Substances (PFAS), Urinary Polycyclic Aromatic Hydrocarbons (UPAHs), trichlorophenol, and many other organics are negatively associated with BMD/BMC levels at specific sites in the human body [28][29][30]. The safety of urban centralized water supply largely relies on water disinfection as it kills pathogens and prevents waterborne infectious diseases.…”
Section: Discussionmentioning
confidence: 99%
“…The current era of rapid global economic development characterized by various industrial processes, including increased production of automobiles, tobacco, cleaning products, building materials, and other household products, has made VOCs more common in the human environment [23][24][25][26][27]. Several studies have demonstrated that some VOCs, such as Perfluoro and Polyfluoroalkyl Substances (PFAS), Urinary Polycyclic Aromatic Hydrocarbons (UPAHs), trichlorophenol, and many other organics are negatively associated with BMD/BMC levels at specific sites in the human body [28][29][30]. The safety of urban centralized water supply largely relies on water disinfection as it kills pathogens and prevents waterborne infectious diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Hologic Inc., Marlborough, MA, USA). BMD was selected in four regions of the femur: the femoral neck, trochanter, intertrochanteric region, and total femur [22].…”
Section: Radiographic Evaluationmentioning
confidence: 99%